Rastafari: the evolution of a people and their identity - Price, Charles (New York University Press, 2022)
"REPI offers a fresh angle on the Rastafari by drawing on underutilized sources such as news stories and colonial records, along with other data such as field notes, interviews and cultural products like screeds and hymns. Charles Price introduces readers to new connections, characters, and events salient to the development of the Rastafari. REPI is a scholarly resource written in a style accessible to a general audience"--